Optimising scour protections: Recent contributions of the ORACLE project - Francisco Taveira Pinto (2021)
Scour protections are a key component of bottom-fixed foundations, namely in gravity based foundations, jacket structures and monopiles commonly used for offshore wind turbines, oil and gas production units and more recently in wave or tidal energy platforms. The cost of the scour protection represents a considerable portion of the capital, operation and maintenance expenditures of the overall investment. Therefore, both the industry and the scientific community devote many studies and research projects focused on its cost-benefit optimisation. In addition, the rising concern of climate change effects and need for lifetime extension of offshore platforms coupled with repowering activities represent new challenges to the design of these elements, which are typically designed to last 25 years, with or without re-filling operations. The ORACLE project has been focused on design optimisation of scour protections in marine environment, by means of improved reliability under long-term conditions. This project includes the physical modelling of optimised dynamic and wide-graded scour protections and the probabilistic assessment and quantification of safety. The present work provides a brief overview of the most recent results of ORACLE. Latest results include the early developments of a new methodology to analyse bathymetric profiles and to compute the damage number and a probabilistic methodology to optimise the median stone diameter of the armour layer.